2007
DOI: 10.1002/art.23137
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage and biomechanical properties of the long bones in Frzb‐knockout mice

Abstract: Objective. Ligands and antagonists of the WNT pathway are linked to osteoporosis and osteoarthritis. In particular, polymorphisms in the FRZB gene, a secreted WNT antagonist, have been associated with osteoarthritis. The aim of this study was to examine cartilage and bone in Frzb ؊/؊ mice. Methods. The Frzb gene in mice was inactivated using a Cre/loxP strategy. Three models of osteoarthritis were used: collagenase, papain, and methylated bovine serum albumin induced. Bone biology was studied using density mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
199
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(219 citation statements)
references
References 42 publications
15
199
1
1
Order By: Relevance
“…Because Dkk-1 inhibits the canonical Wnt pathway, our results are consistent with the observation that targeted deletion of the Frzb gene in mice (Frzb Ϫ/Ϫ ), which results in activation of the canonical Wnt pathway, leads to up-regulation of Mmp3 and causes more severe OA cartilage destruction in response to instability, enzymatic injury, or inflammation (10). Moreover, we have observed that Dkk1 expression is high in undifferentiated mesenchymal cells and is markedly decreased during in vitro chondrocyte differentiation of micromass cultures of mesenchymal cells (35).…”
Section: Dkk-1 Inhibits Experimental Oa 2575supporting
confidence: 90%
See 1 more Smart Citation
“…Because Dkk-1 inhibits the canonical Wnt pathway, our results are consistent with the observation that targeted deletion of the Frzb gene in mice (Frzb Ϫ/Ϫ ), which results in activation of the canonical Wnt pathway, leads to up-regulation of Mmp3 and causes more severe OA cartilage destruction in response to instability, enzymatic injury, or inflammation (10). Moreover, we have observed that Dkk1 expression is high in undifferentiated mesenchymal cells and is markedly decreased during in vitro chondrocyte differentiation of micromass cultures of mesenchymal cells (35).…”
Section: Dkk-1 Inhibits Experimental Oa 2575supporting
confidence: 90%
“…Secreted FRP inhibits the canonical Wnt pathway by binding to Wnt proteins (7). Mutations in sFRP-3, encoded by FRZB, are associated with human OA pathogenesis (8,9), and Frzbknockout mice show more severe OA cartilage destruction in response to instability, enzymatic injury, or inflammation (10). In contrast, Dkk acts by binding to low-density lipoprotein receptor-related protein 5 (LRP-5) and LRP-6 coreceptors (11).…”
mentioning
confidence: 99%
“…It is, however, generally known that meta-analyses have little power to detect relatively rare variants with a modest effect that confer risk in a specific subset of OA cases. Furthermore, functional studies in Frzb-knockout mice showed increased cortical bone thickness and density, resulting in stiffer bones upon mechanical loading, which may increase OA susceptibility and stresses developmental aspects (8).…”
mentioning
confidence: 99%
“…Through its influence on Wnt signaling, FRZB is a powerful and direct modulator of chondrocyte maturation (6). Accelerated cartilage breakdown has been shown to develop in knockout mice deficient in this gene (7). The original study in which an association of FRZB with hip OA was reported involved a cohort of women (8); that study showed that the associated alleles at FRZB reduced the activity of the protein encoded.…”
mentioning
confidence: 99%